Evaluation of Planting Design in Interiors in Terms of Basic Design Principles: The Example of Istanbul Zorlu Shopping Center - Kucukali, Ufuk Fatih (AIS - Architecture Image Studies, 2024)
This study focuses on the importance and value of interior landscaping. Interior landscaping plays a significant role in meeting aesthetic needs in urbanized environments where natural elements are diminishing. Plants are used as natural design elements to complement and enhance artificial spaces. In interior landscaping, it is important to transfer and integrate natural landscapes into indoor spaces. Plants have the ability to shape the environment through appropriate compositions and special designs. The aim of this study is to evaluate interior landscaping from both technical and aesthetic perspectives. It emphasizes the importance of considering the growth conditions, ecological suitability, and selection of visually appealing containers for the plants used in interior design. The methodology of the research includes a literature review, data evaluation, and the assessment of Istanbul Zorlu Center Shopping Mall as a case study. This study aims to contribute to interior design by highlighting the technical and aesthetic aspects of interior landscaping. Selecting the right plants, providing suitable growing conditions, and creating visually appealing arrangements are crucial for interior landscaping. The examination of Istanbul Zorlu Center Shopping Mall as a case study emphasizes the implementation of interior landscaping and its relationship with fundamental design principles.